Objective Features of Administrative Offenses under the Article 443 of the Code of Ukraine on Administrative Offenses and Their Impact on the Scope of Powers of the National Police of Ukraine - V. V. Krykun (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article has stipulates that public relations in the field of labor protection and public health are the generic object of an administrative offense under the Art. 443 of the Code of Ukraine on Administrative Offenses. The legislator has formed a generic object out of two relatively independent parts: 1) public relations on labor protection and 2) public relations on public health. The direct object of an administrative offense under the Art. 433 of the Code of Ukraine on Administrative Offenses can be defined as public relations to protect the population from infectious diseases and ensuring its sanitary and epidemic well-being. The author has established the content of a socially dangerous act, which stipulates administrative liability under the Art. 433 of the Code of Ukraine on Administrative Offenses: 1) violation of the rules provided by the Resolution of the Cabinet of Ministers of Ukraine “On the prevention of the spread of an acute respiratory disease COVID-19 caused by the corona virus SARS-CoV-2 on the territory of Ukraine” dated from March 11, 2020 No. 211; 2) violation of the requirements of regulatory acts (orders, instructions, rules, regulations, etc.) of the Ministry of Health, which establish sanitary-hygienic and sanitary-anti-epidemic rules. The author has established the competition of norms of the Art. 42 of the Code of Ukraine on Administrative Offenses and the Art. 433 of the Code of Ukraine on Administrative Offenses according to the object and socially dangerous act; the author has suggested legislative amendments related to the elimination of the specified collision by the disapplication of the Art. 42 of the Code of Ukraine on Administrative Offenses.